Interdisciplinary Research Burden in Islamic Studies and Action from Academic Librarian - Nuryaman, Nuryaman; Rifai, Agus (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2024)
Interdisciplinary research is increasingly recognized as a crucial approach to addressing the complexity of religious and social issues in regional and global contexts. However, the implementation of such research often encounters significant challenges, particularly in fields like Islamic Studies. Despite its potential, integrating diverse disciplines into Islamic Studies research is not always successful due to various obstacles. With their unique expertise and role as